Effects of"Si"Tactic of Breathing Exercises on Pulmonary Function and Life Satisfaction in Patients with COPD in Stable Phase - Fengguang GUAN; Tao WANG; Yulan HUANG; Tingting LI (康复学报)
Objective:To explore effects of"Si"tactic of breathing exercises on pulmonary function and life satisfaction in stable chronic obstructive pulmonary disease (COPD) patients.Methods:Seventy patients were randomly divided into the observation group and the control group with thirty-five cases respectively. After excluding seven drop-out cases, the observation group remained thirty-one cases and the control group remained thirty-two cases. Two groups were given routine treatment and nursing care in department of respiration, besides the observation group accepted the words"Si"breathing exercises for three months, and the rehabilitation effects of the two groups were respectively assessed by compliance, pulmonary function, Borg Scale and life satisfaction scale.Results:After three months intervention, the compliance of the patients about breathing exercises was 100%. The lung function measured by FEV1showed a significant improvement in the observation group (P=0.00); the scores of Borg Scale were lower than the control group (P<0.05); the scores of life satisfaction were higher than the control group (P=0.00).Conclusion:"Si"tactic of breathing exercises can improve pulmonary function, Borg Scale and life satisfaction for COPD patients in stable stage. The training project is relatively simple, and compliance of the patients is relatively high."Si"tactic of breathing exercises can be recommended as part of the comprehensive pulmonary rehabilitation program in the future.